Influence of functional electrical stimulation of the hamstrings on knee kinematics in stroke survivors walking with stiff knee gait - Martin J. B. Tenniglo (Journal of Rehabilitation Medicine, 2018)

(untitled)
Objective: To explore whether functional electrical stimulation of the hamstrings results in improved knee kinematics in chronic stroke survivors walking with a stiff knee gait. Design: Quasi-experimental. Subjects: Sixteen adult chronic stroke survivors. Methods: Survivors received functional electrical stimulation of the hamstrings, 3 times a week for 1 h during a period of 5 weeks. 3D kinematics was calculated before the training period and after 5 weeks of training. Knee kinematics of walking without stimulation before the training period was compared with walking with stimulation after 5 weeks of training. (intervention effect). In addition, knee kinematics of walking without stimulation before the training period was compared with walking without stimulation after the training period (therapeutic effect). Results: The intervention effect showed a significant increase, of mean 8.7° (standard deviation (SD) 8.3, p = 0.001), in peak knee flexion. The therapeutic effect showed a significant increase in peak knee flexion, of mean 3.1° (SD 4.7, p = 0.021) Conclusion: The results of this exploratory study suggest an increase in knee kinematics in swing after functional electrical stimulation of the hamstrings in stroke survivors walking with a stiff knee gait. The largest improvement in peak knee flexion in swing was seen when participants walked with hamstring stimulation. Participants with low neurological impairment responded better to hamstring stimulation, and there are indications that the effect of hamstring stimulation can be predicted during a single session. The effect of functional electrical stimulation is comparable to that of more invasive treatment options, such as botulinum toxin or soft-tissue surgery. This makes functional electrical stimulation a feasible treatment option for daily clinical practice.